Disseminated Coccidioidomycosis in Africa - Samuel Deokjong Yoo; John K Lusiba; Robert Lukande; Kyungmin Shin (European Journal of Case Reports in Internal Medicine, 2020)
Background: Coccidioidomycosis is an endemic disease in the Americas. No cases have been reported in Africa. Patient: A 23-year-old HIV seronegative Ugandan man was referred to Mulago National Referral Hospital in Kampala, Uganda with a 10-month history of haemoptysis and difficulty breathing, and a 6-month history of localized swellings on the extremities. He had associated weight loss and drenching sweats, but no fevers. He had taken anti-tuberculosis medicine for 2 months with no improvement. He had never travelled out of Uganda. On physical examination, he had cystic swellings and ulcerated lesions on the extremities. He had tachypnoea, crackles in the chest and mild hepatomegaly. Bronchoscopic examination showed two masses occluding the right main bronchus. Bronchoscopic biopsy showed findings consistent with coccidioidomycosis. The patient improved with antifungal treatment and was discharged. Conclusion: We report the first case of disseminated coccidioidomycosis with pulmonary and cutaneous manifestations in Africa.